IMPROVED SOLUBILITY NOVEL MULTICOMPONENT CRYSTALS OF FENOFIBRIC ACID-ACETYLSALISYLIC ACID - Anggraini, Deni; Novita, Gressy; Wulandari, Intan (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Solubility is an important physicochemical property of active pharmaceutical ingredients. Poor water solubility of active pharmaceutical ingredients leads to low bioavailability; therefore, efforts are needed to improve the solubility of active pharmaceutical ingredients. The goal of this study was to prepare and characterize novel multicomponent crystals of fenofibric acid (FA) using acid acetylsalicylic (ACE) as a coformer and to evaluate the solubility enhancement when prepared for multicomponent crystal formation.  Solid characterization of the novel multicomponent crystals was performed using powder X-ray diffraction (XRD), differential scanning diffraction (DSC), Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), polarized microscopy, and solubility tests. Multicomponent crystals were prepared by the solvent drop grinding method using a few drops of an ethanol pro analyzer. The results showed that the solubility of multicomponent crystalline fenofibric acid was 4.7 times greater than that of pure fenofibric acid. Differential Scanning Calorimetry characterization results show the novel multicomponent crystals  with a sharp endothermic peak at 136,65 oC. The PXRD diffractograms show no new diffraction peaks and a decrease  in intensity. FT-IR spectroscopic analysis showed no new functional groups, and most of the transmittance peaks of the multicomponent crystals were superimposed between the peaks of fenofibric acid and acetylsalicylic acid. The novel multicomponent crystals fenofibric acid with acetylsalicylic acid as a coformer can improve the solubility of fenofibric acid  Keywords: Acetylsalicylic acid ; Fenofibric acid ; Multicomponent crystals ; Solubility